GEOGRAPHIC DISTRIBUTION AND INHERITANCE OF «A» TYPE SEED COAT IN BRASSICA RAPA L. POPULATION - A. N. Ignatov; M. E. Pavlova; A. A. Terekhin; K. Hida (Овощи России)
Distribution and inheritance of «A» and «B» types of seed coat in populations of B. rapa originated from Europe, Central Asia, China and Japan was studied. «A» type seeds were found in Central Asian and Japanese populations represented by toria, Asian turnip and plants of «B». rapa ssp. nipposinica (L.H.Bailey) Hanelt. In intraspecific crosses, «A» type of seed coat was controlled by two complementary dominant genes.